Design and Implementation of Environmental Education Workshops with the participation of Environmental Educators in Schools in Guerrero, México - Vences-Martínez, José Angel (2025)
The socio-environmental crisis, understood from various perspectives, drives the need to reorient the role of the environmental educator. This study aimed to implement Environmental Education (EE) workshops to raise awareness and strengthen the knowledge of primary and secondary school students about the proper management of Municipal Solid Waste (MSW). A mixed-methods approach, combining qualitative and quantitative methods, was adopted. The research was carried out in two stages: the first involved training higher education students as environmental educators; the second consisted of implementing participatory workshops in six educational centers. During the initial engagement with the school community, an interview was conducted as part of the participatory diagnosis to identify the main environmental issue, revealing that improper management of MSW was the most significant concern. In response, the environmental educators designed six EE workshops focusing on the integrated management of MSW. The qualitative analysis, based on the systematization of experiences, revealed that playful strategies and active learning were key elements in the success of the strategy. As part of the workshop programming, both diagnostic and final evaluations were administered to the target population, yielding average scores of 6.2 and 9.2, respectively. Likewise, the parametric Student’s t-test was applied, observing significant differences between both evaluations (p < 0.05). In conclusion, through the implementation of workshops by environmental educators, primary and secondary school students acquired the necessary tools for the separation, classification, and proper management of MSW.